Preparedness of Interns of a Private Dental Institution to Be A Part of The Task Force in Pandemic Control - A Questionnaire Survey - B, RESHMI; SAKTHI, D. SRI; S, ARVIND (The journal of contemporary issues in business and government, 2021)
As a normal situation of disease can take over a pandemic role and affect the population around the world,it's necessary for all the doctors and front line officers to be ready to act in case of any emergency at any time. This survey aims to assess the knowledge and attitude of interns, towards handling a pandemic situation without fear and hesitation. This online questionnaire survey containing 15 items were used among 100 interns of a private dental college in chennai. The responses obtained were collected and tabulated in excel and then exported to SPSS, chi square test was used to check the association between gender and knowledge , knowledge and attitude. 13.0% of females had good knowledge when compared to males (4.0%) and 32.0% males had positive attitudes, when compared to 21% females. It can be concluded that a positive attitude in nearly 50% of the study population with fair to poor knowledge, might not make them competent enough in being a part of the task force. Rigorous training and stringent protocols on infection control would prepare the target population for the new normal situation arising in the world